White Matter Changes-Related Gait and Executive Function Deficits: Associations with Age and Parkinson's Disease - Sartor, Jennifer; Bettecken, Kristina; Bernhard, Felix P.; Hofmann, Marc; Gladow, Till; Lindig, Tobias; Ciliz, Meltem; ten Kate, Mara; Geritz, Johanna; Heinzel, Sebastian; Benedictus, Marije; Scheltens, Philip; et al. (Frontiers in Aging Neuroscience, 2017)
Background: White matter changes (WMC) are a common finding among older adults and patients with Parkinson’s disease (PD), and have been associated with, e.g., gait deficits and executive dysfunction. How the factors age and PD influence WMC-related deficits is, to our best knowledge, not investigated to date. We hypothesized that advanced age and presence of PD leads to WMC-related symptoms while practicing tasks with a low complexity level, and low age and absence of PD leads to WMC-related symptoms while practicing tasks with a high complexity level. Methods: Hundred thirty-eight participants (65 young persons without PD (50-69ys, yPn), 22 young PD patients (50-69ys, yPD), 36 old persons without PD (70-89ys, oPn) and 15 old PD patients (70-89ys, oPD)) were included. Presence and severity of WMC were determined with the modified Fazekas score. Velocity of walking under single and dual tasking conditions and the Trail Making Test (TMT) were used as gait and executive function parameters. Correlations between presence and severity of WMC, and gait and executive function parameters were tested in yPn, yPD, oPn and oPD using Spearman’s rank correlation, and significance between groups was evaluated with Fisher’s z-transformed correlation coefficient. Results: yPn and yPD, as well as oPn and oPD did not differ regarding demographic and clinical parameters. Severity of WMC was not significantly different between groups. yPn and yPD displayed significant correlations of WMC with executive function parameters at low levels of task complexity, oPn at intermediate, and oPD at high complexity levels. Conclusion: This study argues for a relevant association of age and PD-related brain pathology with WMC-related gait and executive function deficits.